Integration of Islamic Education Policy in the Context of Malay Culture: An Analysis of Its Implementation and Impact on Educational Management in Indonesia - Anwar, Syafiul; Anwar , Ach. Syafiul; Sutiah, Sutiah (Universitas Islam Negeri Raden Fatah Palembang, 2025)
Policy is a crucial element in the management process, including within the context of Islamic education. Islamic education policies are formulated as efforts to provide solutions to the various challenges faced by educational institutions and to achieve educational objectives oriented towards the moral, spiritual, and intellectual development of students. These policies must undergo a research process that involves various constructive suggestions and can be revised in accordance with evolving situations and challenges. In some cases, policies may need to be modified or refined to ensure the effectiveness of their implementation and better understanding by all stakeholders involved. Islamic education policies also have significant implications for educational management, including aspects of curriculum, teaching methods, and the governance of human resources and educational institutions as a whole. This study analyzes the implementation and implications of Islamic education policies on educational management, aiming to provide recommendations for more effective and adaptive policies. The research findings indicate that Islamic education policies should remain focused on goodness, well-being, and orderliness, while also providing relevant and sustainable solutions for the improvement of the education system in the future.